Histopatologi Usus Halus Mencit Pasca Pemberian Ekstrak Etanol Daun Ashitaba (HISTOPHATOLOGICAL CHANGES ON SMALL INTESTINE OF MICE AGAINS WITH OF THE ETHANOL EXTRACT OF ASHITABA LEAVES) - Wiadnyana, I Made Putra; Budiasa, Ketut; Berata, I Ketut (Buletin Veteriner Udayana, 2015)
The purpose of this research was to know the effects of the ethanol leaf extract ashitaba(Angelica keiskei) against the histopathologicalchanges in the small intestine of mice (Musmusculus). This research used 15 mice (Mus musculus) with in average 25-30 gram and is divided into five group of treatment. Group A, were used as a control (placebo): groups B, C, D, and Eweregiven ashitaba leaf ethanol extract byorally in dose 125 mg/kg bw, 250 mg / kg bw, 500 mg / kgbw, and 1,000 mg/kg bw as long as 21 days respectively. On the 22nd days, all of the mice wasnecropsied and the small intestine tissues was took for the histopathological prepare processing.The results of histopathological examination of the small intestine of mice were fatty degenerationat one mouse in dose 125 mg/kg bw. On the mice by dose of 250 mg/kg bw of treatment, wereshowed fatty degeneration and inflammatory lesions. On the mice by dose 500 mg/kg bw, wereobtained that three of mice were affected fatty degeneration and inflammatory lesions. On the miceby dose 1,000 mg/kg bw were obtained that three of mice suffer  inflammatory lesions. All of thetreatment of this research were not appeared necrose lesion. Conclussion of this research is thetreatment of the ethanol extract of ashitaba leaves by orally at a dose range from 125 mg/kg bw until dose 1,000 mg /kg bw as long as 21 days did not raise the significance histopathologicalchange in the small intestines of mice (Mus musculus).
Keywords: ashitaba (Angelica keiskei); small intestine; mice (Mus musculus)